Factors Contributing towards the Sustainability of Youth Organizations as Partners in Community Development - Hamzah, Azimi; Suandi, Turiman (Universiti Putra Malaysia Press, 1994)
The aim of this qualitative study is to identify factors that contribute towards the sustainability of youth organization as partner in community development. Three major tools were used to secure information: interview, observation and document analysis. The study was conducted at Kampung Endah in the District of Kuala Langat, Selangor. The study revealed 14 factors that contribute to the sustainability of a youth organization as partner in community development. They were administration, leadership, vision, planning, division of task, experience, funding, economic development, people's support, spiritual development, monitoring, linkage with agencies, contribution from community and volunteerism.